Ambiguous luminosity. Issue 1 (1st March 2016) - Zimmer, Jeff
This article is an autobiographical review by Jeff Zimmer discussing his multi-layered illuminated paintings on glass and how the theme of ambiguity threads through his work. Aesthetic and conceptual developments over the past decade are traced in this article, including research on mythological models of ambiguity, connections between seeing and judging reflected in security camera images, the use of the concept of averted vision in the expression of thematic content, the symbolic use of snow as a metaphor for 'whitewashing', and the use of drones to communicate disconnects between action and consequence. His aesthetic development is traced from flat figurative images to multi-layered, three-dimensional (3D) de-populated landscapes.